Ising antiferromagnet with mobile, pinned, and quenched defects - Selke, W.; Holtschneider, M.; Leidl, R. (Condensed Matter Physics, 2005)
Motivated by recent experiments on (Sr,Ca,La)₁₄Cu₂₄O₄₁, a two-dimensional
Ising antiferromagnet with mobile, locally pinned and quenched defects
is introduced and analyzed using mainly Monte Carlo techniques. The interplay
between the arrangement of the defects and the magnetic ordering
as well as the effect of an external field are studied. У зв’язку з недавніми експериментами на (Sr,Ca,La)₁₄Cu₂₄O₄₁, представлено модель двовимірного Ізингівського антиферомагнетика із рухомими, локально закріпленими та замороженими дефектами та проаналізовано її, в основному технікою Монте Карло. Досліджено взаємозв’язок між впорядкуванням дефектів та магнітним впорядкуванням, а також ефект зовнішнього поля.